Water–energy, climate, and habitat heterogeneity mutually drives spatial pattern of tree species richness in the Indian Western Himalaya - Thakur, Shinny; Dhyani, Rupesh; Negi, Vikram S.; Bhatt, Indra D. (Frontiers in Forests and Global Change, 2022)
Analyzing the patterns of plant species richness across a broad geographic gradient is critical for biodiversity conservation and understanding the processes that shape these patterns. We produce a species richness map by stacking the ranges of 51 tree species along an elevation gradient in the western Himalaya using Stacked Species Distribution Models (SSDM) approach. Among various modeling algorithms available in SSDM, Random Forest (RF) and Artificial Neural Networks (ANN) exhibited best performance (r=0.81, p<0.001), thus were used to generate species richness map of trees in the study region. The predicted tree species richness distribution pattern revealed a mid-elevation peak at around 2000 m asl, which is in concordance with the observed richness pattern (R2=0.94, p<0.001). Our findings revealed that the elevational pattern of tree species richness is explained by mutual effect of water-energy availability, climate, and habitat heterogeneity. The study also verifies that the impact of moisture on tree richness coincides geographically with climate factors that increase moisture levels. At higher elevations, water-energy related variables are likely to impact species richness directly, whereas at lower elevations, the effect is more likely to be tied to moisture. As the greatest richness concentrated on mid elevation zone, conservation policies should be implemented in these areas, as they are the most prone to changes in environmental factors.